Evidence of 2024 Summer as the Warmest During the Last Four Decades in the Aegean, Ionian, and Cretan Seas - Yannis Androulidakis; Vassilis Kolovoyiannis; Christos Makris; Yannis Krestenitis (Journal of Marine Science and Engineering)
The summer of 2024 witnessed record-high sea surface temperatures (SST) across the Aegean, Ionian, and Cretan Seas (AICS), following unprecedented air heatwaves over the sea under a long-term warming trend of 0.46 °C/decade for the mean atmospheric temperature (1982–2024). The respective mean SST trend for the same period is even steeper, increasing by 0.59 °C/decade. With mean summer surface waters surpassing 28 °C, particularly in the Ionian Sea, the southern Cretan, and northern Aegean basins, this summer marked the warmest ocean conditions over the past four decades. Despite a relatively lower number of marine heatwaves (MHWs) compared to previous warm years, the duration and cumulative intensity of these events in 2024 were the highest on record, reaching nearly twice the levels seen in 2018, which was the warmest until now. Intense MHWs were recorded, especially in the northern Aegean, with extensive biological consequences to ecosystems like the Thermaikos Gulf, a recognized MHW hotspot. The strong downward atmospheric heat fluxes in the summer of 2024, following an interannual increasing four-decade trend, contributed to the extreme warming of the water masses together with other met-ocean conditions such as lateral exchanges and vertical processes. The high temperatures were not limited to the surface but extended to depths of 50 m in some regions, indicating a deep and widespread warming of the upper ocean. Mechanisms typically mitigating SST rises, such as the Black Sea water (BSW) inflow and coastal upwelling over the eastern Aegean Sea, were weaker in 2024. Cooler water influx from the BSW decreased, as indicated by satellite-derived chlorophyll-a concentrations, while upwelled waters from depths of 40 to 80 m at certain areas showed elevated temperatures, likely limiting their cooling effects on the surface. Prolonged warming of ocean waters in a semi-enclosed basin such as the Mediterranean and its marginal sea sub-basins can have substantial physical, biological, and socioeconomic impacts on the AICS. This research highlights the urgent need for targeted monitoring and mitigation strategies to address the growing impact of MHWs in the region.